An Improved Resource Utilization System for Fog Computing Environment - Nassa, Himani; Kumar, Jitender (International Journal of Computer Sciences and Engineering, 2019)
Fog computing has expanded the horizons of cloud computing services near to the users. Firstly the IoT devices were used exclusively VMs but this results in high energy consumption. At the cloud layer the problem of resource utilization has been practised. But at the Fog layer the problem of Overutilization and Underutilization of resources occur. So, to overcome this problem we are designing a model for resource utilization that achieves best result for both service provider and end users. The current system incorporates an adaptive way for the utilization of resources at the cloud layer. But at the Fog layer the adaptive way of cloud layer are not being practised. The Fog layer allows pre-processing of requests but have limited resources. In order to overcome this problem, this paper, proposes a mechanism for improving the resource utilization at fog computing layer. Our proposed model is not only beneficial for the fog service providers in terms of good resource utilization but also equally beneficial for the fog service users in terms of good response time.